Enumeration on the various tenets in Scene Recognition - Applications and Techniques - Shri Kumar, Bhavesh; Naren, J.; Prahathish, K.; Vithya, G. (International Journal of Psychosocial Rehabilitation, 2024)
Scene recognition is a task of great significance in computer vision. Certainly, it is not very easy due to various factors like cluttered image, poor separation of boundaries in between the scene objects, bad lighting, etc. Hence, the topic receives huge research attention. In this paper, the various applications using Scene Recognition and the various techniques that are incorporated to classify, feature extract and cluster scene images are reviewed.